2015
DOI: 10.1111/febs.13183
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of endothelial‐cell‐mediated vascular repair

Abstract: Maintenance of vascular integrity is essential for the prevention of vascular disease and for recovery following cardiovascular, cerebrovascular and peripheral vascular events including limb ischemia, heart attack and stroke. Endothelial stem/progenitor cells have recently gained considerable interest due to their potential use in stem cell therapies to mediate revascularization after ischemic injury. Therefore, there is an urgent need to understand fundamental mechanisms regulating vascular repair in specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 175 publications
(398 reference statements)
1
49
0
Order By: Relevance
“…The epigenetic control of EC biology, however, is incompletely understood. [2][3][4] Histone methylation is an important mechanism of epigenetic regulation. Trimethylation at histone 3 lysine 4 (H3K4me3), located in promoter regions, is associated with gene expression.…”
mentioning
confidence: 99%
“…The epigenetic control of EC biology, however, is incompletely understood. [2][3][4] Histone methylation is an important mechanism of epigenetic regulation. Trimethylation at histone 3 lysine 4 (H3K4me3), located in promoter regions, is associated with gene expression.…”
mentioning
confidence: 99%
“…These alterations include the post-translational addition or removal of methyl groups to DNA as well as methyl, acetyl, sumoyl and phospho groups to histones and other kind of proteins. These changes participate in remodelling chromatin and modifying its accessibility to transcription factors and cofactors [17]. Epigenetic control is one of the main regulatory systems contributing to phenotypic diferences between cell types in multicellular organisms.…”
Section: Epigeneticsmentioning
confidence: 99%
“…The acetylation status of histone is ine-tuned by histone acetyltransferases (HATs) and HDACs. HDACs are enzymes that remove acetyl groups from histone lysine residues thereby increasing their negative charges, which lead to chromatin condensation and gene repression [17].…”
Section: Histone Modiicationmentioning
confidence: 99%
“…Despite their remarkable potential for vascular regeneration in several diseases, clinical trials using EPCs have only been moderately successful (Fadini et al, 2012). However, the main obstacle to improving their vascular repair function could be a lack of understanding of the transcriptional network regulating their differentiation and proangiogenic activity (Fraineau et al, 2015).…”
Section: Epigenetic Modulation Of Epc Functions In Chfmentioning
confidence: 99%
“…Although a number of studies have shown that the process of histone acetylation/deacetylation plays a critical role in vascular development and ECs differentiation, little is known about EPCmediated vascular repair regulation by HATs and HDACs (Fraineau et al, 2015).…”
Section: Histone Modificationsmentioning
confidence: 99%